K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 9 2020

(7x + 3)(4x + 2) = 28x2 - 15

=> 7x(4x + 2) + 3(4x + 2) = 28x2 - 15

=> 28x2 + 14x + 12x + 6 - 28x2 + 15 = 0

=> (28x2 - 28x2) + (14x + 12x) + (6 + 15) = 0

=> 26x + 21 = 0

=> 26x = -21

=> x = -21/26

9 tháng 9 2020

\(28x^2+14x+12x+6=28x^2-15\) 

\(26x+6=-15\) 

\(26x=-21\) 

\(x=-\frac{21}{26}\)

5 tháng 8 2016

\(x^3-4x^2-8x+8\)

\(\Leftrightarrow\left(x^3-4x^2\right)-\left(8x-8\right)\)

\(\Leftrightarrow x^2\left(x-4\right)-4\left(x-4\right)\)

\(\Leftrightarrow\left(x-4\right)\left(x^2-4\right)\)

18 tháng 9 2016

\(frac\{3}{4}\)

8 tháng 7 2015

x2-7x+12

=x2-3x-4x+12

=x(x-3)-4(x-3)

=(x-3)(x-4)

x4-4x2+4x-1

=x4-1-4x2+4x

=(x2-1)(x2+1)-4x(x-1)

=(x-1)(x+1)(x2+1)-4x(x-1)

=(x-1)[(x+1)(x2+1)-4x]

=(x-1)(x3+x2+x+1-4x)

=(x-1)(x3+x2-3x+1)

6x4-11x2+3

=6x4-2x2-9x2+3

=2x2(3x2-1)-3(3x2-1)

=(3x2-1)(2x2-3)

 

19 tháng 6 2021

a, \(\left(x-15\right)\left(x+15\right)-\left(x+2\right)^2-\left(x-5\right)^2\)

\(=x^2-225-x^2-4x-4-x^2+10x-25\)

\(=-x^2+6x-254\)

b, \(\left(2x-1\right)\left(2x+1\right)+\left(x+9\right)^2-\left(x-3\right)^2\)

\(=4x^2-1+x^2+18x+81-x^2+6x-9=4x^2+24x+71\)

c, \(\left(7x-3\right)^2-\left(x-5\right)\left(x+5\right)-\left(2x+4\right)^2\)

\(=49x^2-42x+9-x^2+25-4x^2-16x-16=44x^2-58x+18\)